2018
DOI: 10.1111/sltb.12444
|View full text |Cite
|
Sign up to set email alerts
|

Veteran Participation in Intensive Suicide Research Protocols: No Evidence of Iatrogenic Effects

Abstract: Suicide research remains fraught with ethical and methodological issues, including researchers' reservations about conducting intensive suicide research protocols due to potential iatrogenic effects and liability concerns. Such issues significantly impede scientific inquiry related to suicide. To date, no research has explored potential iatrogenic effects of intensive, nontreatment suicide research among Veterans. This study aimed to fill this gap. It was hypothesized that participation in suicide-specific pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Echoing these findings, Bender and colleagues 17 showed that higher-risk individuals actually exhibited lower implicit suicidality after suicidality assessment. Many other studies have detected similar patterns 13 , 18 , 19 . In terms of utilitarian ethics, evidence indicates that suicide research is ethical because its potential harms appear to be consistent with minimal risk and may be outweighed by its potential benefits (e.g., advancing knowledge, reducing suicidality).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Echoing these findings, Bender and colleagues 17 showed that higher-risk individuals actually exhibited lower implicit suicidality after suicidality assessment. Many other studies have detected similar patterns 13 , 18 , 19 . In terms of utilitarian ethics, evidence indicates that suicide research is ethical because its potential harms appear to be consistent with minimal risk and may be outweighed by its potential benefits (e.g., advancing knowledge, reducing suicidality).…”
supporting
confidence: 65%
“…Moreover, the mechanisms commonly considered to lead to increased risk for suicide after exposure to suicide stimuli (e.g., habituation, sensitization, and priming) typically exert the strongest influence immediately after exposure. Prior studies did not detect increased suicide risk or related harms within session or within days of exposure 13 , 18 . Given that it is possible that effects on relatively rare phenomena such as suicide ideation and attempt may require a longer period to evidence, the present study extends prior research by examining short- and long-term effects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Per the protocol, if a participant rated their current intent to kill themselves at a 4 or higher, mood induction tasks were employed to reduce distress or a provider was alerted. UWRAP score changes have been used in previous research to assess distress following research participation (Poindexter et al., 2019; Reynolds et al., 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, a recent meta-analysis found that exposure to suicide-related research content may actually be associated with small reductions in distress (Blades, Stritzke, Page, & Brown, 2018). Recent studies have sought to explicitly assess potential distress following participation in suicide-focused research, finding no significant increases in distress following completion of suicide-related self-report measures, clinical interviews, or in-lab tasks (Ammerman, Sorgi, Berman, Coccaro, & McCloskey, 2018; Eynan et al., 2014; Gibson, Boden, Benson, & Brand, 2014; Poindexter, Nazem, Barnes, Hostetter, & Smith, 2019; Reynolds, Lindenboim, Comtois, Murray, & Linehan, 2006). Studies exploring the effects of participating in suicide-related research have predominately utilized online study designs or included participants with remote risk histories (see review by Dazzi et al., 2014).…”
mentioning
confidence: 99%